NICRA Project and Its Impact on Farmer’s Practices – A Study in Cachar District of Assam: Assessing the Impact of the NICRA Project on Farmer's Practices in Cachar District, Assam (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Climate change has become an important area of concern for India to ensure food and nutritional security for growing population. The impacts of climate change are global, but countries like India are more vulnerable in view of the high population depending on agriculture. In India, significant negative impacts have been implied with medium-term (2010-2039) climate change, predicted to reduce yields by 4.5 to 9 percent, depending on the magnitude and distribution of warming. Since agriculture makes up roughly 16 percent of India’s GDP, a 4.5 to 9 negative impact on production implies a cost of climate change to be roughly up to 1.5 percent of GDP per year. The Government of India has accorded high priority on research and development to cope with climate change in agriculture sector. With this background, the ICAR has launched a major Project entitled, National Initiative on Climate Resilient Agriculture (NICRA) during 2010-11 with an outlay of Rs.350 crores for the XI Plan. The project aims to enhance resilience of Indian agriculture to climate change and climate vulnerability through strategic research and technology demonstration. The research on adaptation and mitigation covers crops, livestock, fisheries and natural resource management. The project consists of four components viz. Strategic Research, Technology Demonstration, Capacity Building and SponsoredCompetitive Grants. The project has made significant initial impact and was well received in most of the districts. Technologies such as on-farm water harvesting in ponds, supplemental irrigation, introduction of early maturing drought tolerant varieties, paddy varieties tolerant to sub-mergence in flood prone districts, improved drainage in water logged areas, recharging techniques for tube wells, site specific nutrient management and management of sodic soils, mulching, use of zero till drills were enthusiastically implemented by the farmers in NICRA villages across the country. The intervention which found tremendous support across the country was the custom hiring centres. The NICRA project has been implemented in the five districts of Assam namely Dhubri, Cachar, Sonitpur, Dibrugarh and Karbiyanglong. In Cachar NICRA project was implemented by the KVK in the year 2011-12 till 2016-17. Under NICRA project in Cachar district various technologies were demonstrated in the site such as varieties which are flood tolerant, short duration varieties to escape flood situations, generation of subsidiary income etc. Many technologies have been widely accepted by the farmers. Despite various constraints while implementation of the project it left a significant impact on farmer’s practices.